Flow simulations on modified aero-propellers - Nathanael, Joshua Christian (2017)
In this project, steady airflow is simulated around a propeller using the CFD software Fluent from ANSYS Student. The propellers for the simulations were a model propeller and a modified propeller with sawtooth serrations at its trailing edge. The fluid domain was built around the propeller and meshed with different settings while maintaining the number of cells in the mesh did not exceed the given limit from ANSYS Student. Flow simulations were then run on Fluent for different flow velocities using a medium mesh, a fine mesh, and a medium mesh with body and face element sizing, for both original model propeller and modified propeller. The results such as the thrust and power coefficients, velocity and pressure distribution, and acoustic power level were compared between the propellers and the meshes.